2002
DOI: 10.1046/j.1523-1755.2002.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cysteine rich protein 61 (CYR61, CCN1) in urine following renal ischemic reperfusion injury

Abstract: The secreted, cysteine-rich, heparin binding protein Cyr61 is rapidly induced in proximal straight tubules following renal ischemia, and excreted in the urine where it might serve as an early biomarker of renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
99
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 40 publications
5
99
1
1
Order By: Relevance
“…Also, CCN1/ CYR61 was induced in proximal straight tubules following ischemic reperfusion injury of the kidney (35). In the obstructed bladder, expression of CCN2/CTGF and CCN1/CYR61 were also induced (36).…”
Section: Discussionmentioning
confidence: 96%
“…Also, CCN1/ CYR61 was induced in proximal straight tubules following ischemic reperfusion injury of the kidney (35). In the obstructed bladder, expression of CCN2/CTGF and CCN1/CYR61 were also induced (36).…”
Section: Discussionmentioning
confidence: 96%
“…Muramatsu et al (2002) demonstrated that cysteine-rich protein 61, a secreted growth factor-inducible immediate early gene, is induced in proximal straight tubules of rodents within 2 hr of renal ischemia and can be detected in rat urine as early as 3-6 hr after renal injury. Cystatin C is a 13-kDa plasma protein that inhibits cysteine proteases and is freely filtered at the glomerulus.…”
Section: Discussionmentioning
confidence: 99%
“…Certain blood and urine markers of kidney injury such as serum creatinine, urea nitrogen as well as urine markers such as casts, fractional excretion of Na are insensitive and nonspecific for the diagnosis of acute kidney injury (32). Recently, urinary molecules have shown promise in both urine and animal studies including, neutrophil gelatinase associated lipocalcin (NGAL) (33,34), Kidney Injury Molecule-1 (Kim 1) (35,36), sodium/hydrogen exchanger isoform 3 (NHE3) (37), cytokines (38,39) cysteine rich protein 61 (40), actin (38), glutathione-Stransferases (41,42). These biomarkers have a great deal of promise in the ability to detect early kidney injury and aid with its subsequent management but need to be validated and confirmed in larger studies.…”
Section: Discussionmentioning
confidence: 99%